SERUM THYROTROPIN CONCENTRATIONS ARE NOT PREDICTIVE OF AGGRESSIVE BREAST CANCER BIOLOGY IN EUTHYROID INDIVIDUALS - Villa, Natalie M. (Endocr Pract, 2015)
OBJECTIVE: The potential influence of hypothyroidism on breast cancer remains incompletely understood. The objective of this study was to investigate the relationship between serum thyrotropin [thyroid-stimulating hormone (TSH)] concentration and markers of aggressive breast cancer biology, as defined by receptor expression profile, tumor grade, and American Joint Committee on Cancer (AJCC) stage characteristics. METHODS: This was a retrospective cohort study of patients from 2002–2014. All breast cancer patients who had complete receptor (estrogen receptor, ER; progesterone receptor, PR; and Her2/neu) and pre-diagnosis serum TSH data (n=437) were included. All patients had one of six receptor profiles: ER+ PR+ Her2/neu −, ER+ PR− Her2/neu−, ER+ PR+ Her2/neu+, ER+ PRHer2/ neu+, ER− PR− Her2/neu+, ER− PR− Her2/neu−. Log-transformed serum TSH concentrations were analyzed using multinomial and logistic regressions for a potential relationship with markers of breast cancer aggressiveness. RESULTS: Increasing serum TSH concentration was associated with a lower probability of having the receptor expression profile ER+ PR+ Her2/neu+ compared to patients with the ER+ PR+ Her2/neu− profile (OR=0.52, p=0.0045). No significant associations between other receptor expression profiles and serum TSH concentration were found. All time-weighted and unweighted median serum TSH concentrations were within normal limits. No significant associations between serum TSH concentration and tumor grade, overall AJCC stage, or tumor size (T), lymph node positivity (N), or presence of metastasis (M) were observed. CONCLUSIONS: Serum TSH was not associated with markers of breast cancer aggressiveness in our cohort.